2021
DOI: 10.3389/fvets.2021.687967
|View full text |Cite
|
Sign up to set email alerts
|

Employability as a Guiding Outcome in Veterinary Education: Findings of the VetSet2Go Project

Abstract: This paper presents a mini-review of employability as a guiding outcome in veterinary education—its conceptualisation, utility, core elements and dimensions, and pedagogical approaches—through a summary of the findings of a major international project with the same aims (the VetSet2Go project). Guided by a conception of the successful veterinary professional as one capable of navigating and sustainably balancing the (sometimes competing) needs and expectations of multiple stakeholders, the project integrated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Work satisfaction in terms of Team culture and Learning possibilities was higher in participants from the UK compared to the other countries. Research by Cake et al demonstrated that, when setting out in their career, veterinary graduates are motivated not only by affiliations with animals, but are also attracted by the prospect of intellectual challenges and being able to interact with others ( 45 ). It stands to reason, therefore, that whenever veterinary practices actively promote professional development opportunities and foster an atmosphere of social support, they are being rewarded with veterinary professionals who are more satisfied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work satisfaction in terms of Team culture and Learning possibilities was higher in participants from the UK compared to the other countries. Research by Cake et al demonstrated that, when setting out in their career, veterinary graduates are motivated not only by affiliations with animals, but are also attracted by the prospect of intellectual challenges and being able to interact with others ( 45 ). It stands to reason, therefore, that whenever veterinary practices actively promote professional development opportunities and foster an atmosphere of social support, they are being rewarded with veterinary professionals who are more satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…It stands to reason, therefore, that whenever veterinary practices actively promote professional development opportunities and foster an atmosphere of social support, they are being rewarded with veterinary professionals who are more satisfied. In the UK, veterinary practices have been actively encouraging veterinary staff programs, focusing on the development of both technical and “soft” skills ( 45 ). Additional research should determine whether these types of programs might be more effective than professional development programs in other countries in terms of enhancing levels of work satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Murdoch University Veterinary School in Australia has integrated a course into the veterinary undergraduate curriculum called Veterinary Professional Life (VPL), which trains students in self‐awareness, psychology and communications skills (Mills et al ., 2006). One of the designers of this programme, Martin Cake, has also written on the importance of these skills in the employability of veterinary graduates (Cake et al ., 2019). The VPL programme was in part derived from, and partnered with, the Veterinary Leadership Experience (Veterinary Leadership Institute, n.d.) which has been used by the Washington State University College of Veterinary Medicine since 2002.…”
Section: Solutions and Resourcesmentioning
confidence: 99%
“…The most cited professional skills needed to be a successful veterinarian are: effective communication, ethics and law, leadership and teamwork, business and finance, personal management, lifelong learning, and employability. 1,5,6,9,14,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Research on developing veterinary professional skills curricula is limited, but there is research about specific professional skills, the value of teaching them, how to effectively teach and assess them, and the different perspectives on which skills are important. 9,26,27,30,[36][37][38]40,41 Much of the research has been in a North American, European, and Australasian context.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6,9,14,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Research on developing veterinary professional skills curricula is limited, but there is research about specific professional skills, the value of teaching them, how to effectively teach and assess them, and the different perspectives on which skills are important. 9,26,27,30,[36][37][38]40,41 Much of the research has been in a North American, European, and Australasian context. 6,9,14,23,[42][43][44] However, some argue that specifically because professional skills are dependent on the context, time, culture and societal needs, a single shared definition is not appropriate, 1,4,22,32,45 and professional skills have been found to vary across geographic, cultural and societal contexts.…”
Section: Introductionmentioning
confidence: 99%